Sporadic Creutzfeldt-Jakob disease in the United Kingdom: analysis of epidemiological surveillance data for 1970-96. - Cousens, S. N. (1997)
OBJECTIVE: To identify changes in the occurrence of Creutzfeldt-Jakob disease that might be related to the epidemic of bovine spongiform encephalopathy. DESIGN: Epidemiological surveillance of the United Kingdom population for Creutzfeldt-Jakob disease based on (a) referral of suspected cases by neurologists, neuropathologists, and neurophysiologists and (b) death certificates. SETTING: England and Wales during 1970-84, and whole of the United Kingdom during 1985-96. SUBJECTS: All 662 patients identified as sporadic cases of Creutzfeldt-Jakob disease. MAIN OUTCOME MEASURES: Age distribution of patients, age specific time trends of disease, occupational exposure to cattle, potential exposure to causative agent of bovine spongiform encephalopathy. RESULTS: During 1970-96 there was an increase in the number of sporadic cases of Creutzfeldt-Jakob disease recorded yearly in England and Wales. The greatest increase was among people aged over 70. There was a statistically significant excess of cases among dairy farm workers and their spouses and among people at increased risk of contact with live cattle infected with bovine spongiform encephalopathy. During 1994-6 there were six deaths from sporadic Creutzfeldt-Jakob disease in the United Kingdom in patients aged under 30. CONCLUSIONS: The increase in the incidence of sporadic Creutzfeldt-Jakob disease and the high incidence in dairy farmers in the United Kingdom may be unrelated to bovine spongiform encephalopathy. The most striking change in the pattern of Creutzfeldt-Jakob disease in the United Kingdom after the epidemic of bovine spongiform encephalopathy is provided by the incidence in a group of exceptionally young patients with a consistent and unusual neuropathological profile. The outcome of mouse transmission studies and the future incidence of the disease in the United Kingdom and elsewhere, will be important in judging whether the agent causing bovine spongiform encephalopathy has infected humans.